The Effect of Intellectual Capital and Executive Compensation on Financial Performance - Leny Suzan; Hanifah Khadrinur (UNIVERSITAS PAKUAN, 2023)
This study aims to determine the effect of intellectual capital and executive compensation on financial performance in Basic Materials Sector Companies listed on the IDX based on financial statement data for 201 8-2021. The data was tested using the panel data regression method. The population used is Basic Materials Sector companies listed on the Indonesia Stock Exchange (IDX) during 2018-2021. This study used purposive sampling method and obtained 35 companies during 4 years of observation. The results of this study show that intellectual capital as measured by VAIC has a positive and significant effect on financial performance and partial executive compensation also affects financial performance. Companies in the basic materials sector are expected to provide internal evaluations to maximize the management of intellectual capital owned and the efficiency of using company assets to improve financial performance in order to be able to foster competition in companies in the basic materials sector. Issuers should also take into account the level of executive compensation for key management in order to advance the financial performance of an issuer by (agent).